An empirical analysis of the time poverty–food insecurity nexus from the perspectives of paid and unpaid work - Edward Martey; Isaac Koomson (Journal of Agriculture and Food Research)
Considering the dynamism in time usage and the need to accumulate resources to smoothing household food consumption overtime, many households suffer from time poverty. This notwithstanding, the empirical link between time poverty and food insecurity is yet to be explored from the perspectives of paid and unpaid work. This study examines the effect of time poverty on food insecurity using a comprehensive household-level data from Ghana Overall, we find that unpaid work-induced time poverty worsens food insecurity by 0.420 standard deviation while time poverty emanating from paid work reduces food insecurity by 0.213 standard deviation. This finding is consistent across several endogeneity-correcting methods and robust to alternative conceptualisations of time poverty. For different locations and age cohorts, both constructs of time poverty influence food insecurity more among urban households and those headed by adults. Our analyses further reveal that household asset accumulation serves as a potential channel via which both forms of time poverty affect food insecurity.